A memória nas páginas do Jornal A União: características para reconhecimento como patrimônio cultural - Barboza, Thalyta Braga (2023)
Dissertation on memory in the pages of the newspaper A União and the characteristics for its recognition as cultural heritage is a social contribution, for this is a printed newspaper with 129 years of existence that has gone through several historical events. This is a research that approaches the newspaper A União as a place of memory, in which the question of its listing as cultural historical heritage is raised.The problematization of the research is precisely what characterizes the newspaper A União as a space of memory for recognition as cultural heritage. The general objective of this study was to discuss the characteristics of the newspaper A União as a space of memory, with a view to its recognition as cultural heritage. The specific objectives were: i) to present the newspaper A União from the historical record and previous studies from the perspective of Information Science; ii) articulate concepts and definitions of memory in the light of agencies heritage and preservation of cultural property; iii) Outline and discuss the characteristics of the newspaper A União, as a place of memory, from the prerequisites of analysis of cultural heritage with a view to recognition as national cultural heritage; iv) to make a sample of the newspaper library, by means of a catalog with three images from each year of the newspaper A União. For this, initially, a bibliographic survey on memory and cultural heritage was carried out.The research was bibliographic, documental, systematic literature and interactive. In addition, it had a sample of specimens of the newspaper covers in Appendix C, from the last 130 years. Therefore, it was possible to inform what is cultural heritage and what is the relevance of memory for Information Science. That is, this research is of great value to expand scientific knowledge in the area of memory and cultural heritage.